Standardisation in engineering surveys - Yavuz, Erol; Ersoy, Nihat (Geodesy and Cartography, 2012)
Buying, selling and changing goods and services easily in today’s world, where economic, social and cultural relations are very complicated, are related to standards that determine the qualities of them. Although, there are standards for every kind of goods and services produced in the European Community (that we still try to be a member of it), any detailed study on this subject has not been done. Unfortunately, conformity packages, which come help us almost in every subject, will force us to work on this subject imperatively. Since the engineering surveys are also based on technological service and its production, getting more quality in a production process and the quality of the personnel (surveying engineers, surveying technicians etc), who works in production process, depend on standardisation of the methods and the equipment used for survey. The subject of the qualification and the quality of personnel, who work in surveying sector, determination of standards related to survey methods and instruments has not been taken into consideration in detail. Only some legal regulations have been developed until now. Quality problem in the production of goods and services must not change from country to country. This subject is very important and cannot be solved by legal regulations made in different countries. Free circulation of goods and services is possible if they are standardised globally.First published online: 03 Aug 2012